Effect of an Acute Incremental Exercise on Plasma Peptide YY, Neuropeptide Y and IGF-1 Concentrations in Young Athletes - Hassan Faraji; Rahman Rahimi; Saeed Dabbagh Nikookheslat (The Society of Aging and Physical Activity (SAPA), 2014)
This study aims to determine the effect of a single exhausting exercise on plasma PYY, NPY and IGF-1 in young athletes. Thirty-one young athletes (aged 19.52±2.75 years, body mass 79.24±16.13 kg, height 173±6.49 cm, and body fat 16.37±5.92%) volunteered to participate in this study. The participations, in randomized crossover manner, performed a single exercise bout on a cycle ergometer at 50 watts (W) for five-minute, and the power output was increased by 30 W every 3 minute until voluntary exhaustion. Venous blood samples were collected before (Pre), immediately after (Post) and 1h after (1h Post) exercise to assess plasma PYY, NPY and IGF-1concentrations. Plasma PYY (p=0.042) and IGF-1 (p=0.001) significantly increased at Post exercise. Also, NPY was increased Post (p=0.001) and for 1h Post (p=0.021) exercise. The exhausting exercise increase plasma PYY concentration and this increase may relate to IGF-1 signals in young athletes. However, increased plasma NPY may not be related to stimulation food intake because it does not penetrate the blood-brain barrier.